PENDIDIKAN INKLUSIF BAGI SISWA BERKEBUTUHAN KHUSUS DI KALIMANTAN SELATAN - Amka (Jurnal Pendidikan dan Kebudayaan, 2019)
Indonesia education law mandates that schools are required to accept all students including students with special educational needs (SEN). This article explains the situation of inclusive education in schools in South Kalimantan Province. This study aims to find out and analyze the implementation of inclusive education policies in the view of principals, management of inclusive education by teachers, and public perceptions of inclusive education. The mixed-methods sequential explanatory design was used in this study by combining face-to-face surveys and interviews. Primary data was obtained from surveys conducted on 100 principals, 500 teachers, and 45 parents of students with special needs and interviews with a number of stakeholders. The results of the study show that local government policies have created the development of inclusive education in schools in South Kalimantan. Most principals support the implementation of inclusive classes, most teachers are willing to work with students with special needs, and parents of regular students accept the concept of inclusive. In practice, the implementation of inclusive education differs from one school to another depending on the perception of the principal and the willingness of teachers in terms of how to implement inclusive education. Abstrak Undang-undang menyatakan bahwa sekolah diharuskan untuk menerima semua siswa termasuk siswa berkebutuhan pendidikan khusus. Artikel ini menyoroti situasi pendidikan inklusif di sekolah-sekolah di Provinsi Kalimantan Selatan. Penelitian ini bertujuan untuk mengetahui dan selanjutnya menganalisa implementasi kebijakan pendidikan inklusif oleh Kepala Sekolah, manajemen pendidikan inklusif oleh guru, dan persepsi masyarakat tentang pendidikan inklusif. Pendekatan metode gabungan yang dinamakan dengan mixedmethods sequential explanatory design digunakan dalam penelitian ini dengan menggabungkan survei tatap muka dan wawancara. Data primer diperoleh dari survei yang dilakukan terhadap 100 kepala sekolah, 500 guru, dan 45 orang tua siswa berkebutuhan khusus serta wawancara dengan sejumlah pemangku kepentingan. Hasil penelitian menunjukkan bahwa kebijakan pemerintah daerah telah menghasilkan pengembangan pendidikan inklusif di sekolah-sekolah di Kalimantan Selatan. Sebagian besar kepala sekolah mendukung penerapan kelas inklusif, sebagian besar guru bersedia bekerja dengan siswa berkebutuhan khusus, dan orang tua siswa reguler menerima konsep inklusif. Dalam praktiknya, pelaksanaan pendidikan inklusif bervariasi dari satu sekolah ke sekolah lain tergantung pada persepsi kepala sekolah dan kemauan guru dalam hal bagaimana menerapkan pendidikan inklusif.